IMPLIKASI KESETIAAN BERIBADAH DALAM PEMBENTUKAN KARAKTER RELEGIUS REMAJA DI GEREJA TORAJA JEMAAT MORIA ULUSALU KLASIS ULUSALU - Gusti Somalinggi; Yulianti; Natalia (CV. ADIBA AISHA AMIRA, 2023)
Implications of Faitfulness to Worship in the Formation of the Religious Character of adolescents in the Toraja Church the Ulusalu Classist Moria Church”. This paper aims to determine the impact of devotion to worship in the formation of the religious character of adolescents who faithfully worship.The research method used in this study is a qualitative method that is descriptive using data analysis. Data collection techniques woth observation and interview techniques. Based on observations and interviews with teenagers, parents of teenagers, and Sunday school teachhers who teach teenagers will have good religious character, the religious character in question is piety to God. Where in faithful worship youth become closer to God, increase knowledge of God’s Word, and make the heart calm.